PLANNING OF SOCIO-ECONOMIC DEVELOPMENT OF REGIONS - Niazova R. T.; Beishenalieva L. B. (Vestnik Issyk-Kulʹskogo universiteta)
The article is devoted to socio-economic planning in the regions of Kyrgyzstan and its significance for sustainable development. The main socio-economic issues are discussed, such as economic inequality between regions, population migration, and limited access to education and healthcare services. Strategic goals and specific planning objectives are identified, including raising living standards, developing agriculture, creating jobs, improving infrastructure, and protecting the environment. The article describes planning methods such as SWOT analysis, program-targeted approaches, and partnerships with international organizations and NGOs. Priority areas such as the agricultural sector, tourism, digitalization, and support for small businesses are highlighted. In conclusion, the challenges and prospects for implementing plans are discussed, emphasizing the need for a long-term strategy to enhance regional competitiveness and improve the quality of life for the population.